Nuclear translocation of plasma membrane protein ADCY7 potentiates T cell-mediated antitumour immunity in HCC - Chen, Jianan; Jiang, Youhai; Hou, Minghui; Liu, Chunliang; Liu, Erdong; Zong, Yali; Wang, Xiang; Meng, Zhengyuan; Gu, Mingye; Su, Yu; Wang, Hongyang; Fu, Jing (Gut, 2025)
BackgroundThe potency of T cell-mediated responses is a determinant of immunotherapy effectiveness in treating malignancies; however, the clinical efficacy of T-cell therapies has been limited in hepatocellular carcinoma (HCC) owing to the extensive immunosuppressive microenvironment.ObjectiveHere, we aimed to investigate the key genes contributing to immune escape in HCC and raise a new therapeutic strategy for remoulding the HCC microenvironment.DesignThe genome-wide in vivo clustered regularly interspaced short palindromic repeats (CRISPR) screen library was conducted to identify the key genes associated with immune tolerance. Single-cell RNA-seq (scRNA-seq), flow cytometry, HCC mouse models, chromatin immunoprecipitation and coimmunoprecipitation were used to explore the function and mechanism of adenylate cyclase 7 (ADCY7) in HCC immune surveillance.ResultsHere, a genome-wide in vivo CRISPR screen identified a novel immune modulator-ADCY7. The transmembrane protein ADCY7 undergoes subcellular translocation via caveolae-mediated endocytosis and then translocates to the nucleus with the help of leucine-rich repeat-containing protein 59 (LRRC59) and karyopherin subunit beta 1 (KPNB1). In the nucleus, it functions as a transcription cofactor of CCAAT/enhancer binding protein alpha (CEBPA) to induce CCL5 transcription, thereby increasing CD8+ T cell infiltration to restrain HCC progression. Furthermore, ADCY7 can be secreted as exosomes and enter neighbouring tumour cells to promote CCL5 induction. Exosomes with high ADCY7 levels promote intratumoural infiltration of CD8+ T cells and suppress HCC tumour growth.ConclusionWe delineate the unconventional function and subcellular location of ADCY7, highlighting its pivotal role in T cell-mediated immunity in HCC and its potential as a promising treatment target.